Development of Mussaenda frondosa sepal infused functional tea with enhanced antioxidant and alpha-amylase inhibitory activities - Nafla Faleel; Thilini Kananke; Namal Perera (Discover Food)
Abstract Mussaenda frondosa (MF) is an edible species of the genus Mussaenda (Rubiaceae) that contains a wide array of medicinal compounds. The present study was conducted to evaluate the physicochemical and functional properties of the MF sepals and to develop a novel herbal tea with improved functional properties. Remarkably high antioxidant and α-amylase inhibitory activities were exhibited by water and ethanol extracts of MF, attributed to their high phenolic and flavonoid contents. None of the extracts showed toxicity, as evaluated by the brine shrimp lethality assay. A tea was formulated by blending different proportions (30, 40 and 50%) of dry sepals of MF with black tea. The sensory analysis showed a significantly high level of acceptance for the formula containing 40% MF (MFT-40) with augmented phenolic contents (138.82 ± 0.21 mg GAE/g), antioxidant (DPPH scavenging activity with IC50 of 12.23 ± 0.45 µg/mL), and hypoglycemic activities (α-amylase inhibition with IC50 of 104.80 ± 0.59 µg/mL) compared to the black tea control (with the values of 128.47 ± 0.13 mg GAE/g, 18.70 ± 0.68 µg/mL and 153.07 ± 0.61 µg/mL respectively). This study revealed the potential use of MF as a source of antioxidants for the development of new functional teas with enhanced health benefits.